Fasting and postprandial glucose, insulin, leptin, and ghrelin values in preterm babies and their mothers: relationships among their levels, fetal growth, and neonatal anthropometry. (May 2015) - Kahveci, Hasan; Laloglu, Fuat; Kilic, Omer; Ciftel, Murat; Kara, Mustafa; Laloglu, Esra; Yildirim, Abdulkadir; Orbak, Zerrin; Ertekin, Vildan; Cesur, Yasar
Abstract Objective: To investigate relationship between anthropometric values of premature babies with their's glucose, insulin, leptin, and ghrelin at birth and on day 15. Methods: We analyzed fasting and postprandial glucose, insulin, leptin, and ghrelin levels at birth and on day 15 in babies born prematurely between 24 and 37 weeks, and who did not have serious problems aside from prematurity at birth. Results: Fasting glucose, insulin, leptin and ghrelin values of babies at birth and on day 15 were significantly lower than postprandial values (all p values p < 0.001). There were positive correlations between the mean insulin, leptin, and ghrelin levels with the gestational age, birth weight, body mass index, head circumference of babies at birth, and anthropometric values on day 15 (all r values > 0.400, all p values < 0.05). Fasting glucose, leptin, and ghrelin values of mothers birth were significantly lower than post-prandial values (all p values p < 0.05). Conclusions: The positive correlations between the insulin, leptin, and ghrelin values of babies at birth with gestational age and anthropometric values suggest that both hormones play important roles in fetal and neonatal growth and development.